PENGARUH TABUNGAN TERHADAP PENINGKATAN DANAPIHAK KETIGA (DPK) BANK PEMBANGUNAN DAERAH KALIMANTAN TIMUR PADA TAHUN 2010 – 2012 - , Mardiana, Yandi Juliandi , ELFREDA A.LAU (EKONOMIA, 2015)
Now that the basic problem in this paper is whether there is influence between savings consist of savings simpeda, al amin savings, savings freshman and my savings to fund third parties on BPD Kaltim from 2010 until 2012, and the variables which influence the dominant of third-party funds.The first hypothesis is the hypothesis that the variables are used to explain the existence of third-party funds BPD Kaltim, hypotheses second, third, fourth and fifth variables simpeda savings, savings al amin, saving my freshman and saving significant effect on third party funds BPD Kaltim period 2010 - 2012 , where the variable savings freshman has a more dominant influence of third-party funds BPD Kaltim period 2010-2012.This study aims to find out whether the model is used to explain the existence of third party funds in BPD Kaltim, the variables consist of variables simpeda savings, savings al amin, savings freshman and my savings are significantly influential on third party funds BPD Kaltim period 2010 - 2012, and to know which variables are most influential to gain greater BPD Kaltim.Analysis tools used in this study are multiple linear regression analysis, assisted by using SPSS statistical software.Basic theory used in this study is Accounting, Financial Management, Financial Institutions, Banks, Financial Statement, Definition and Types of Sources of Funds Bank.But when do the research can be concluded that the model used to predict the existence of third-party funds savings BPD Kaltim and tend to move up from year to year and still give a great contribution to the third-party funds BPD Kaltim.